The Science Canopy: Religion, Legitimacy, and the Charisma of Science - LEWIS, JAMES R. (Temenos - Nordic Journal for the Study of Religion, 2010)
Academics usually think of religion as legitimating other social institutions. However, one often finds apologists appealing to the authority of science as a strategy for supporting the truths of their particular tradition. In a social environment where diverse religious claims compete with each other, it is probably inevitable that different groups seek alternate sources of legitimacy. Science is an attractive legitimator because of its prestige and because of the popular view of science as an objective arbiter of ‘truth’. After examining the notion of ‘legitimation strategies’ derived from Max Weber’s discussion of the legitimation of authority, the article analyzes the specific ways in which religious groups appeal to the authority of science.